A Historical Note on the Assimilation Rates of Foreign-Born Men and Women in the U.S. - Harriet Duleep; Dan Dowhan; Xingfei Liu; Mark Regets; Robert Gesumaria (Global Labor Organization (GLO), 2025)
The 1924 Immigration Act excluded immigrants from economically developing countries to the point of their near total exclusion. Forty years later, the 1965 Immigration and Nationality Act eliminated most discriminatory county-of-origin barriers. America's doors opened and immigration from economically developing countries soared. Fueling debates about the "quality" of immigrants from economically developing countries, empirical studies based on a wellrespected methodology conclude that post-1965 immigrant men have low initial earnings and sluggish earnings growth. This methodology is based on flawed assumptions (Duleep, Liu, and Regets, 2022). Removing these assumptions reveals high earnings growth for post-1965 immigrant men in accordance with the Immigrant Human Capital Investment Model (Duleep and Regets, 1999). A similar story emerges for immigrant women, contradicting the Family Investment Hypothesis first put forth by Long (1980) and Duleep and Sanders (1993). It appears a pre- 1965/post-1965 transition occurred in the earnings profiles of U.S. immigrants, from earnings resembling those of U.S. natives to low initial earnings but much higher earnings growth than their U.S.-born statistical twins. The transition underlies the overtime success story of immigrant families from economically developing countries (Duleep, Regets, Sanders, and Wunnava, 2021); the high earnings growth reflects human capital investment that invigorates the economy (Duleep, Jaeger, and McHenry, 2018; Green, 1999, Green and Worswick, 2012).
Additional information: Forthcoming in Research in Labor Economics
Keywords: J15; J16; J24; J31; C1; 330; Immigrant earning growth; human capital investment; skill transferability; immigrant quality; sample restrictions; family investment hypothesis; nonparametric estimation